Spotlight on Learning from Failure Corporate Disinformation and the Changing Face of Attacks with Renee DiResta and Robert Matney - DiResta, Renee; Matney, Robert (O'Reilly Media, Inc., 2019)
Disinformation campaigns have targeted political and social movements around the world. The crosshairs of influence operations have expanded to include high-visibility brands and large enterprises. Responsible corporate leaders must be prepared to defend hard-won brand reputation and equity. In this edition of Spotlight on Learning from Failure, learn how influence operations are manifesting in 2019 as they've moved beyond politics. Renee DiResta and Robert Matney, coauthors of the US Senate report about Russian disinformation operations, will take you through specific examples of disinformation campaigns affecting brands and discuss the high-level social and corporate implications of the erosion of public trust and public discourse in our information ecosystem. Recorded on July 23, 2019. See the original event page for resources for further learning. Find future live events to attend or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Learning from Failure, you'll discover the lessons learned from failures both large and small. You'll discover how successful companies have addressed setbacks, missteps, and challenges and how you can grow from their examples.